Type of training has a significant influence on the GH/IGF-1 axis but not on regulating miRNAs - Khalid, Katarzyna; Szewczyk, Artur; Kiszałkiewicz, Justyna; Migdalska- Sęk, Monika; Domańska-Senderowska, Daria; Brzeziański, Michał; Lulińska, Ewelina; Jegier, Anna; Brzeziańska-Lasota, Ewa (Biology of Sport, 2020)
The growth hormone (GH)/insulin-like growth factor-1 axis is responsible for glucose homeostasis. In the present study we assessed the expression levels of miRNA-124, miRNA-210 and miRNA-375 and immunoexpression of IGFBP-3 in relation to the concentrations of IGF-1 and glucose in athletes performing different types of effort. Sixty-six young male athletes (age 25.4±4.1 years) were divided into: group EN (33 male athletes; age 25.6±4.4 years) with endurance-type efforts (disciplines: triathlon, long distance running, cycling) and group ST (33 male athletes; age 25.2±3.9 years) with strength-type efforts (disciplines: weightlifting, body building, CrossFit). The control group consisted of 28 non-training men (age 29.1±4.7 years). Statistically significantly higher IGF-1 concentration and lower glucose concentration (P 0.05). Levels of expression of miRNA-210 and miRNA-375 were higher in athletes vs. controls (P>0.05). The obtained data confirmed the importance of the somatotropic axis in the regulation of metabolic adaptation to physical exercise. The detected variation in the concentrations and expression levels of the studied molecules involved in the somatotropic axis in athletes confirmed the role of the somatotropic axis in adaptation to physical effort. Statistically significant reduction of glucose concentration and the highest expression of IGF-1in serum in athletes suggest the anabolic effect of IGF-1 through insulin receptors on many tissues under the influence of moderate physical exercises (mainly during resistance training).